DOWNRIGHT AND APPARENT APPRAISAL ON QUALITY BY DESIGN: A GOAL-ORIENTED APPROACH - RIDDHI PATEL; OM BAGADE; BINDIYA PATEL; KULDEEP RAMTEKE (International Journal of Pharma and Bio Sciences, 2014)
Design process has one of the most important factors that contributing in pharmaceutical product quality. The pharmaceutical industry is has used the modern concept of Quality by Design (QbD) to apply science based manufacturing principles for new and existing products to assure quality of the formulation and to increase efficiencies, provide regulatory relief and flexibility, and offer important business benefits throughout the product life cycle. It supports both industry and FDA to move towards a more scientific, risk based, holistic and proactive approach to pharmaceutical development. It is also a major challenge to the Pharmaceutical industry whose processes are fixed in time, despite inherent process and material variability, In case of designing and development of a product, it is essential to define desire product performance profile viz-a-viz Target product Profile (TPP), Target Product Quality Profile (TPQP)] and identify critical quality attributed (CQA). On that basis we used to design the product formulation and process to meet the requirements for product attributes which pretend to ascertain and recognise the impact of raw materials such as critical material attributes (CMA)], critical process parameters (CPP) on the CQAs and identification and control sources of variability.